Water quality and trophic status in main rivers of Thailand - Leelahakriengkrai P. (2014)
The water quality and trophic status monitoring in the main rivers of Thailand during all three seasons in March 2008, August 2008 and January 2009 were investigated. Water samples were collected from 6 regions in Thailand which differed in geological and useful characteristics. In northern Thailand, the Ping River was selected; in the central region, the Tha Chin River; in the northeast region, the Chi River; in the eastern region, the Chanthaburi River; in the western region, the Kwai River and in the southern region, the Tapee River. Samples were taken from the upper, middle and lower parts of each river. At each site, some physical and chemical parameters were studied and the water quality was classified based on its trophic status. It was found that the water quality at most of the sampling sites were not clearly different and could be classified as clean-moderate water quality (oligotrophicmesotrophic status). However, the water quality at some sampling sites were different, especially, upstream of the Ping and Tapee Rivers which could be classified as clean (oligotrophic status) and downstream of the Tha Chin River showed moderate to polluted water quality (mesotrophic-eutrophic status).